1988
DOI: 10.1507/endocrj1954.35.833
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Subacute Thyroiditis Over 10 Years after the First Attack in Three Cases.

Abstract: We saw a total

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 9 publications
1
19
1
1
Order By: Relevance
“…rence of SAT with HLA B35 has also been reported (13)(14)(15) (4,16,17). Another report (17) and our data suggested that the presence of antithyroid autoantibodies was not correlated with the recurrent…”
Section: F I G U R E 1 ( A) Ag E D I S T R I B U T I O N O F P a T supporting
confidence: 73%
“…rence of SAT with HLA B35 has also been reported (13)(14)(15) (4,16,17). Another report (17) and our data suggested that the presence of antithyroid autoantibodies was not correlated with the recurrent…”
Section: F I G U R E 1 ( A) Ag E D I S T R I B U T I O N O F P a T supporting
confidence: 73%
“…The recurrent episodes were similar to the first episodes of SAT. The titers of various viral antibodies were not increased during the clinical course of recurrence (39). In a larger study that evaluated data for 3,344 patients with SAT between 1970 and 1993, SAT recurred in 48 of 3,344 patients (1.4%) (mean, 14.5 Ϯ 4.5 yr after the first episode).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies used blood Tg concentrations as a marker of the early phase of SAT [13][14][15]. Another study identified high blood concentrations of interleukin-6 in thyrotoxic patients, but the levels returned to within the normal range after remission [16].…”
Section: Discussionmentioning
confidence: 99%